The IMPLEMENTASI KEBIJAKAN KURIKULUM PENDIDIKAN MI AL-BIRRA PEKANBARU: Kebijakan Kurikulum Islam - Asni Yerti, Nisya Frasetia (Fakultas Studi Islam Universitas Muhammadiyah Riau, 2023)
The research objective was to answer problems regarding the implementation of curriculum policies implemented at MI Al Birra Pekanbaru related to the implementation of principal policies that implemented the 2013 curriculum. The research aims to determine the policy of principals implementing the 2013 curriculum at MI Al Birra Pekanbaru. The curriculum improves quality, namely by applying new concepts in learning. The application of the curriculum is not easy to apply universally, which requires socialization and a process of experience and increases students' abilities in knowledge, attitudes, skills. It is hoped that students will be more creative, innovative and more productive. The method used in this research is qualitative, with descriptive research and determination of information using a survey and getting into of the school by means of interviews, observation and documentation at the MI Al Birra school in Pekanbaru. The results showed that the implementation of the educational curriculum policy at MI Al Birra Pekanbaru had implemented an educational curriculum in accordance with the provisions set by the Ministry of Religion (Ministry of Religion) so that the learning process could run efficiently and effectively. Keywords : Implementation, Educational curriculum policies, MI Al-Birra Pekanbaru